2021
DOI: 10.1080/00313831.2020.1869074
|View full text |Cite
|
Sign up to set email alerts
|

Increased Metacognition About Health and Learning in a Middle School-based Health Promotion Project Using an Action-oriented Research Model

Abstract: Health is a resource for pupils' learning. Including health in the curriculum and teaching will enable pupils to understand the connection between health and learning. Action research has proved to be effective from a learning perspective. Our purpose was to explore whether, and how, using action-oriented research methods in a middle school-based health promotion project contributed to metacognition about health and learning. The design was an action-oriented research model using reflection forums: a support g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Only three of the seven programs obtained expected results, generating positive effects in students towards the development of healthy habits. From the programs presented above, results have been extracted that agree with the study carried out by [17], programs for the promotion of healthy habits have been found to take account of the school's programming so that they can be carried out effectively, without overloading teachers. The planning and inclusion of health education in the school curriculum give it the continuous and integrated character that any knowledge requires to be acquired and integrated.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Only three of the seven programs obtained expected results, generating positive effects in students towards the development of healthy habits. From the programs presented above, results have been extracted that agree with the study carried out by [17], programs for the promotion of healthy habits have been found to take account of the school's programming so that they can be carried out effectively, without overloading teachers. The planning and inclusion of health education in the school curriculum give it the continuous and integrated character that any knowledge requires to be acquired and integrated.…”
Section: Discussionsupporting
confidence: 57%
“…The contribution of [15] affirms that for a health program to work, it is necessary that it be adapted to the context in which it is going to be implemented, moreover, they consider that this aspect is key if educational centers are to be a true HpS. The programs should not be implemented as something specific that is developed in certain circumstances, since health promotion must be part of the ideology and culture of the center, it must be a priority that must be addressed daily in the classroom, either as a specific subject [16] or in a transversal way [17]. Its value and relevance should prioritize its approach, giving time and opportunities for its internalization [16].…”
Section: Programs That Promote Healthmentioning
confidence: 99%
“…Action research is performed in close collaboration with practice, and the purpose is to understand and improve practice based on a scientific approach (Fals‐Borda, 1991; Stringer & Genat, 2004). The action‐oriented model (Nilsson Lindström & Bringsén, 2021) in this project aimed to increase pupil influence by their participation in all project steps, through giving the pupils the possibility to express their opinion, be listened to and listen to others and be involved in and influence planning. The action‐oriented model consists of a support group, a project group, activities in classes and a focus group with teachers.…”
Section: Methodsmentioning
confidence: 99%
“…Pupil influence in health promotion projects in schools is beneficial for the health resources for pupils’ learning and achievement in school (Nilsson Lindström & Bringsén, 2021). However, the implementation of health promotion activities and projects in schools is usually carried out separately from teaching.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation